هيكل الضرائب والنمو الاقتصادي خارج المحروقات: دراسة حالة الجزائر ()3 - قجاتي, قجاتي; كمال, سي محمد (Finance and Business Economies Review, 2017)
<span dir="ltr" style="left: calc(var(--scale-factor)*78.02px); top: calc(var(--scale-factor)*454.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.976403);" role="presentation">The goal of this study is to evaluate tax composition in Algeria, suggests the impact of different <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*467.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.947119);" role="presentation">components of tax revenue (direct and indirec<span dir="ltr" style="left: calc(var(--scale-factor)*245.57px); top: calc(var(--scale-factor)*467.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932916);" role="presentation">t tax revenue, as percentage of <span dir="ltr" style="left: calc(var(--scale-factor)*376.27px); top: calc(var(--scale-factor)*467.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954703);" role="presentation">total tax revenue) on non- <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*480.91px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91034);" role="presentation">hydrocarb<span dir="ltr" style="left: calc(var(--scale-factor)*94.34px); top: calc(var(--scale-factor)*480.91px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919294);" role="presentation">ons economy an empirical study using a Generalized Method of Mom<span dir="ltr" style="left: calc(var(--scale-factor)*375.43px); top: calc(var(--scale-factor)*480.91px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914692);" role="presentation">ent model the period 1992- <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*494.11px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906907);" role="presentation">2015. <span dir="ltr" style="left: calc(var(--scale-factor)*78.02px); top: calc(var(--scale-factor)*507.31px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.995095);" role="presentation">The direct taxes are significant and positively impact on economic growth, while indirect <span dir="ltr" style="left: calc(var(--scale-factor)*464.38px); top: calc(var(--scale-factor)*507.31px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.857539);" role="presentation">taxes <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*520.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.875366);" role="presentation">parameter <span dir="ltr" style="left: calc(var(--scale-factor)*100.26px); top: calc(var(--scale-factor)*520.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925123);" role="presentation">are a negative sign and influence on non-<span dir="ltr" style="left: calc(var(--scale-factor)*269.69px); top: calc(var(--scale-factor)*520.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909853);" role="presentation">hydrocarbon<span dir="ltr" style="left: calc(var(--scale-factor)*320.11px); top: calc(var(--scale-factor)*520.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929938);" role="presentation">s economy, though insignificant. Results <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*533.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.981131);" role="presentation">obtained from our study exhibit that value-<span dir="ltr" style="left: calc(var(--scale-factor)*236.09px); top: calc(var(--scale-factor)*533.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963823);" role="presentation">added tax is more sensible to economic and socio-<span dir="ltr" style="left: calc(var(--scale-factor)*452.02px); top: calc(var(--scale-factor)*533.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.985803);" role="presentation">political <span dir="ltr" style="left: calc(var(--scale-factor)*53.88px); top: calc(var(--scale-factor)*547.03px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903012);" role="presentation">variables.